2021
DOI: 10.1063/5.0036178
|View full text |Cite
|
Sign up to set email alerts
|

Core level photoelectron spectroscopy of heterogeneous reactions at liquid–vapor interfaces: Current status, challenges, and prospects

Abstract: Liquid-vapor interfaces, particularly those between aqueous solutions and air, drive numerous important chemical and physical processes in the atmosphere and in the environment. X-ray photoelectron spectroscopy is an excellent method for the investigation of these interfaces due to its surface sensitivity, elemental and chemical specificity, and the possibility to obtain information on the depth distribution of solute and solvent species in the interfacial region. In this Perspective, we review the progress th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 239 publications
(200 reference statements)
0
73
0
Order By: Relevance
“…This is in contrast to the situation with valence LJ-PES, which has been far less explored 2, 44,45 despite the primary importance of the lowest-ionization energies in driving aqueous-phase chemistry. 2 In this case, after more than 15 years of active high-energy-resolution LJ-PES research 38,43 (and with concomitant advancement of aqueous electronic structure calculations and spectral simulation methods 8,9,41,[46][47][48][49][50][51][52] ), an experimental advance and alternative terminology must be adopted to enable unequivocal and accurate valence VIE determinations with respect to the vacuum level. Related developments are needed to permit E F (or system chemical potential) energy referencing of LJ-PES spectra, robust eΦ extractions from liquid samples, and direct comparisons of liquid-and solid-phase absolute-scale electronic energetics.…”
Section: Lj-pes From Water and Aqueous Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to the situation with valence LJ-PES, which has been far less explored 2, 44,45 despite the primary importance of the lowest-ionization energies in driving aqueous-phase chemistry. 2 In this case, after more than 15 years of active high-energy-resolution LJ-PES research 38,43 (and with concomitant advancement of aqueous electronic structure calculations and spectral simulation methods 8,9,41,[46][47][48][49][50][51][52] ), an experimental advance and alternative terminology must be adopted to enable unequivocal and accurate valence VIE determinations with respect to the vacuum level. Related developments are needed to permit E F (or system chemical potential) energy referencing of LJ-PES spectra, robust eΦ extractions from liquid samples, and direct comparisons of liquid-and solid-phase absolute-scale electronic energetics.…”
Section: Lj-pes From Water and Aqueous Solutionmentioning
confidence: 99%
“…Unfortunately, there is little data available to clarify this issue, despite multiple works attempting to quantify the interfacial density profiles of the different atomic ions in aqueous solutions. 38,76,88,89 In this context, some of the authors have recently reported that concentrated electrolytes, despite changing the electronic structure of water, do not appear to lead to any significant relative energy shifts between different valence photoelectron peaks. 7 Rather, the lowest-energy ionization (1b 1 ) peak slightly broadens, with an accompanied apparent narrowing or energy-gap reduction of the split second ionization (3a 1 ) feature, the latter being the more notable spectral change.…”
Section: Changes Of Solvent Vie and Solute Vie Values In Aqueous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The present work considers interfacial anion hydration in the context of solution-phase photoelectron spectroscopy via liquid microjets. [56][57][58][59][60][61] Relative to gas-phase photoelectron spectroscopy, interpretation of the microjet results is subject to several interrelated issues regarding probing depth, 28,56,59 the energy-dependent nature of the electron attenuation length, [62][63][64] and the inelastic mean free path of the outgoing photoelectron. 62 Scattering of the outgoing electron imparts a dependence on the wavelength of the photodetachment laser, [65][66][67][68][69] with changes in peak shapes for near-threshold photoionization.…”
Section: Introductionmentioning
confidence: 99%
“…In water, the electron attenuation length ranges from 1-10 nm depending on the electron's kinetic energy, 59,63 suggesting that liquid microjet photoelectron spectroscopy is interface sensitive, 61 albeit with significant contributions from beyond the first monolayer of solvent. 73 Whereas interfacial effects on the photochemistry 74 and ultraviolet spectroscopy 75,76 of small aqueous solutes have been demonstrated, there has been no systematic investigation of whether VIEs themselves are sensitive to the presence of the air/water interface; the only detailed studies concern the rather unique case of the hydrated electron.…”
Section: Introductionmentioning
confidence: 99%